An Overview on Time-Resolved Optical Analysis of HiPIMS Discharge - Britun, Nikolay; Konstantinidis, Stephanos; Snyders, Rony (Plasma processes and polymers, 2015)
The progress in the time‐resolved characterization of HiPIMS discharges performed during the last decade in our group is overviewed. Optical emission and absorption spectroscopy, as well as laser‐induced fluorescence‐based techniques have been mainly utilized. The results covering such important aspects of the HiPIMS discharge as the density evolution of the discharge species, their ionization and excitation, propagation of secondary electrons in the discharge volume, dynamics of velocity distribution of the discharge species, gas rarefaction, etc. are discussed. The two‐dimensional distributions of Ti and Ti ion density as a typical example of sputtered particles in HiPIMS discharge. This figure demonstrates spatial complementarity of neutral and ionized sputtered atoms in the discharge volume at low pressure (5 mTorr). The paper mainly deals with temporal and spatial behavior of the ground state species in HiPIMS discharges.